LOCAL CONTENT PROMOTION IN FORMING MALANG CITY PUBLIC LIBRARY LIBARARY'S BRAND EQUITY - Mahdi, Reza; Ramadhan, Fery Wahyu (Edulib, 2019)
Local content is content that is owned by a library with a particular subject, for example the local content of a city or regional public library is a collection of books and non-book libraries that talk about the city or area of the library. But for the Public Library of Malang City, local content is divided into two types, namely collections of authors from Malang and collections that talk about Malang. The local content of Malang City Public Library must be highlighted, one of them is by doing a promotion, to become a differentiator of the public library with other public libraries. This research is a qualitative research with descriptive method. Data retrieval is done by observing and interviewing the librarians of Malang City Public Library and Malang Community.